SOSIALISASI PROGRAM KELUARGA HARAPAN (PKH) BIDANG KESEHATAN DI KECAMATAN SIANTAR BARAT KOTA PEMATANGSIANTAR - RIRIS SURYANI RUMAPEA; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
By improving the quality of Human Resources (HR) is one effort of government to bring number of poverty down. So, Government through Social Ministry formulated Program Keluarga Harapan. Program Keluarga Harapan is cash conditional transfer program. Pematangsiantar became one region of target implementation of this program in 2014. As a new program, Program Keluarga Harapan needs to be socializated as the beginning of implementation. The purpose of this research is to describe and analyze Program Keluarga Harapan especially in health sector.The theory concept that used is theory by Laswell. This theory consist of five components; the communicator, the contents of message, the media used, the communicant, and last the effects after socialization. This research used qualitative research methods to describe data. The needed data was collected through observation, interview, and literature study.After the research, it was found that socialization was optimal. Because few of RTSM as receiver change their mindset by checking up their health to destinated health facility.Keyword : Socialization, Program Keluarga Harapan, Health